POSITIONING OF THE RAILWAY SYSTEM IN OSIJEK’S SPATIAL PLANS 1912-2019 (Advances in Civil and Architectural Engineering, 2021)
This article focuses on the history of Osijek’s spatial and urban planning with respect to the position and treatment of the city’s railway system. The study compared eight plans, dating from 1912 to the present day, and found that railway construction in and around the city was completed in 1910. During this period, three different planning approaches were developed for the city’s railway system. The oldest planning approach, starting in 1912, was a passive, “leave it as it is” approach, dealing cautiously with the network of newly constructed railway lines. The second, proactive approach, proposed dismantling or relocating railway lines from the city center while the third approach focused on the actual railway traffic in Osijek with respect to public use of vacant railway corridors. The results will help provide a scientific basis for future planning of railways and railway corridors in the urban area of Osijek.